Modifikasi Perilaku Menunda Tugas pada Mahasiswa Melalui Teknik Reinforcement Positif - Durratu Safrah; Endang Setyaningsih (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Academic procrastination or the behavior of delaying tasks is a chronic problem frequently faced by university students, leading to detrimental effects on both academic performance and psychological well-being. This study aims to empirically examine the effectiveness of applying positive reinforcement techniques through a self-management method to reduce the duration of academic task procrastination among college students. A quantitative approach with a Single-Case Experimental Design (SCED) using an A-B-A pattern was employed over a 28-day period. The subjects consisted of three active college students selected via purposive sampling, all scoring high on the Procrastination Assessment Scale-Students (PASS). Data regarding the duration of task delay were collected daily using a self-monitoring log. Visual analysis of the graphs indicated a highly significant decrease in procrastination duration for all three subjects during the intervention phase (B), with an accumulative reduction percentage exceeding 70% from the baseline. During the withdrawal phase (A2), the duration of task delay remained low and stable. This study concludes that positive reinforcement techniques are effective in modifying and reducing task-delaying behavior among college students by shifting the subjects' focus from anxiety avoidance to the attainment of positive reinforcers. The newly formed adaptive behavior proved to be enduring due to the internalization process of new study habits.